Representation of multiple objects in macaque category-selective areas - Pinglei Bao (Nature Portfolio, 2018)
Inferotemporal cortex (IT) neurons respond to specific objects but the precise neural mechanisms for clutter-invariant representation is not known. Here the authors show that face and body patch IT neurons respond to multiple objects with winner-take-all, contralateral-take-all or weighted averaging depending on the stimulus properties.